Association between Dyslipidemia Patterns and Early Cardiovascular Complications among Adults. A Cross-Sectional Clinical Study - NIAZI, ATTAULLAH KHAN; ABBAS, MUHAMMAD UMAR; ABBAS, AIMEN; SAJJAD, MUHAMMAD SHAHZAIB; JUMADIN, ANEELA; ABDULLAH, HARIS (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Dyslipidemia is a significant risk factor that is not only majorly modifiable but also a cardiovascular disease (CVD) risk factor in South Asian populations due to the tendency to develop atherogenic lipid patterns at a younger age. Cardiovascular complications such as diastolic dysfunction, carotid intima-media thickness (CIMT) increase, subclinical ischemia and early ventricular remodeling usually proceed undetected. To enhance preventive cardiology, it is important to understand the association between the various patterns of dyslipidemia and early cardiac abnormalities. Objectives: to establish the correlation between dyslipidemia trends and early heart diseases in adults. Methods: A cross-sectional study was carried out on 100 adults aged 30-70 years, in terms of clinical data. After an overnight fast, detailed lipid profiles (TC, LDL-C, HDL-C, TG) were determined. The patterns of dyslipidemia were divided into isolated elevated LDL-C, isolated hypertriglyceridemia, low HDL-C and mixed dyslipidemia. Each participant had ECG and echocardiography to determine the early cardiovascular involvement, such as the diastolic dysfunction, enlargement of the CIMT, LV hypertrophy, decreased EF, and silent ischemic alterations. The SPSS 26 version was used to analyses the data, and Chi-square and logistic regression were used to evaluate the associations. Results: Dyslipidemia was found in 72 percent of the participants and early cardiovascular problems were detected in 38 percent. Mixed dyslipidemia presented the most significant correlation (64.7%), then isolated high LDL-C (40.9%), and low HDL-C (33.3%). Early cardiac abnormalities were observed in only 10.7% of people having normal lipid profiles. Conclusion: Mixed dyslipidemia and high LDL-C are channels with high predictivity of early cardiovascular complications. Lipid profiling must be regularly incorporated into cardiovascular risk measurement to help identify the problem early and provide preventive care on time.